Analysing of players’ perceptions on game aesthetics - Mai, Li-Chuan Evelyn; Long, Shuling; Yuan, Yuan; Fu, Kun (Frontiers in Communication, 2025)
Game aesthetics is a crucial multidimensional concept in understanding player experience within the gaming industry. However, limited empirical research has examined how players perceive game aesthetics and to what extent these perceptions vary among different player groups. To address this gap, this study employed a quantitative approach to identify the measures and the key dimensions of game aesthetics in Action Role-Playing Games (ARPGs), adopting the Mechanics–Dynamics–Aesthetics (MDA) framework to assess players’ perceptions of game aesthetics. A survey was conducted with 462 valid respondents who had prior experience playing ARPGs. The results demonstrated that the “Aesthesis” dimension was perceived as the most important aspect of game aesthetics, followed by “Story,” “Venture,” and “Connection.” These results indicate that visual and auditory design, narrative content, gameplay structure, and social interaction are key factors influencing players’ aesthetic experiences. Furthermore, ARPG Players with different educational backgrounds, game experiences, monthly game expenses, and playtime may perceive game aesthetics differently. Players’ perceptions of game aesthetics were also found to influence their acceptance of games, which subsequently affects their willingness to purchase or recommend them to others.